Genetic diversity analysis of Pasteurella multocida isolates from alpacas with clinical signs of pneumonia - Rímac B., Rocío (2017)
The purpose of this study was to characterize strains of Pasteurella multocida isolated from lungs of 1-2 months old alpacas with signs of pneumonia, collected in 2014. The BOX-PCR technique was used to demonstrate genetic diversity among strains. Twenty-four strains of P. multocida were isolated from 46 animals through biochemical identification tests. The BOX-PCR analysis showed two amplified band patterns, where 22 strains were grouped in one cluster and two strains in another cluster. The present study showed genetic homogeneity in most of the strains, evidencing a common source of infection that affected the animals.